Metabolic and microbial responses to the complexation of manuka honey with α-cyclodextrin after simulated gastrointestinal digestion and fermentation. (April 2017) - Parkar, Shanthi G.; Jobsis, Carel M.H.; Herath, Thanuja D.; Stoklosinski, Halina M.; van Klink, John W.; Sansom, Catherine E.; Sims, Ian M.; Hedderley, Duncan I.
Highlights: Effect of complexation of manuka honey on its metabolic fate was examined in vitro. Complexation protected honey monosaccharides from upper gut digestion. Complexation modulated faecal microbial metabolism and lactate generation. Complexed honey fermenta inhibited the growth of enteropathogenic Salmonella . Abstract: Manuka honey (MH), α-cyclodextrin (C) and a formulation containing these two components (MH + C) were subjected to simulated gastrointestinal digestion followed by fermentation with human faecal microbiota. The honey monosaccharides, glucose and fructose were 9- and 3-fold higher respectively in the digesta of MH + C compared with MH. Methylglyoxal (MGO), characteristic of MH was absent after gastric digestion. The precursor of MGO, 1, 3-dihydroxyacetone was found to be at a higher concentration in MH + C, compared with MH, after digestion. The MH + C fermenta were more acidic (pH 4.6, p < 0.05), with a higher lactate concentration ( p < 0.005). Compared with water control, MH + C fermenta significantly inhibited Salmonella enterica Typhimurium ( p = 0.041) and enhanced Lactobacillus reuteri ( p = 0.016). These findings suggest that complexation with α-cyclodextrin protects some MH components during digestion. This increases the availability of substrates to faecal bacteria resulting in the generation of metabolites that favour gut health.